EFEKTIVITAS PEMANFAATAN SISTEM ONLINE TRADING SYARIAH DALAM MENINGKATKAN INVESTOR SAHAM DI PASAR MODAL SYARIAH - Herlina Yustati (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2017)
Investment can be interpreted as an action that is accommodated by generating future profits. If the first orangutan with tangible assets such as land, buildings, livestock and others, then in the present there is an investment through financial instruments such as deposits, balance sheets, buying and selling of shares, and others. Both types of investments have the same goal of generating profit. Financial instruments such as sharia shares have been developed using the Syariah Online Trading System (SOTS), so that transactions can be made anywhere as long as the market is open. Through SOTS, investors have easy access and improved service quality so that the number of investors increased by 2341% compared to 2012 when SOTS was launched in 2011. And the number of sharia investors also increased by 2.3% from total investors in capital market in year 2016